Primary results from the CLEAR study of a novel stent retriever with drop zone technology - Yoo, Albert; Geyik, Serdar; Froehler, Michael T.; Maurer, Christoph Johannes; Kass-Hout, Tareq; Zaidat, Osama O.; Nogueira, Raul G.; Hanel, Ricardo A.; Pierot, Laurent; Spelle, Laurent; Lopes, Demetrius; Hassan, Ameer; et al. (Journal of neuroInterventional surgery, 2023)
Background Challenges to revascularization of large vessel occlusions (LVOs) persist. Current stent retrievers have limited effectiveness for removing organized thrombi. The NeVa device is a novel stent retriever designed to capture organized thrombi within the scaffold during retrieval. - Objective To evaluate the safety and effectiveness of revascularization of acute LVOs with the NeVa device. - Methods Prospective, international, multicenter, single-arm, Investigational Device Exemption study to evaluate the performance of the NeVa device in recanalizing LVOs including internal carotid artery, M1/M2 middle cerebral artery, and vertebrobasilar arteries, within 8 hours of onset. Primary endpoint was rate of expanded Treatment in Cerebral Ischemia (eTICI) score 2b-3 within 3 NeVa passes, tested for non-inferiority against a performance goal of 72% with a −10% margin. Additional endpoints included first pass success and 90-day modified Rankin Scale (mRS) score 0-2. Primary composite safety endpoint was 90-day mortality and/or 24-hour symptomatic intracranial hemorrhage (sICH). - Results From April 2021 to April 2022, 139 subjects were enrolled at 25 centers. Median National Institutes of Health Stroke Scale (NIHSS) score was 16 (IQR 12-20). In the primary analysis population (n=107), eTICI 2b-3 within 3 NeVa passes occurred in 90.7% (97/107; non-inferiority P<0.0001; post hoc superiority P<0.0001). First pass eTICI 2b-3 was observed in 73.8% (79/107), with first pass eTICI 2b67-3 in 69.2% (74/107) and eTICI 2c-3 in 48.6% (52/107). Median number of passes was 1 (IQR 1-2). Final eTICI 2b-3 rate was 99.1% (106/107); final eTICI 2b67-3 rate was 91.6% (98/107); final eTICI 2c-3 rate was 72.9% (78/107). Good outcome (90-day mRS score 0-2) was seen in 65.1% (69/106). Mortality was 9.4% (13/138) with sICH in 5.0% (7/139). - Conclusions The NeVa device is highly effective and safe for revascularization of LVO strokes and demonstrates superior first pass success compared with a predicate performance goal. - Trial registration number NCT04514562.